The influence of whistleblowing systems and internal audit on fraud prevention: evidence from PT Angkasa Pura Indonesia - Lubis, Muhammad Arif; Mayasari, Ima (Enrichment : Journal of Management, 2025)
Fraud represents a critical threat to organizational integrity, particularly within state-owned enterprises in Indonesia. This study aims to examine the influence of whistleblowing systems and internal audit on fraud prevention in PT Angkasa Pura Indonesia. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the research evaluates the relationships of whistleblowing and internal audit to fraud prevention. Data were collected via a structured questionnaire and validated through reliability and validity tests. The findings reveal that whistleblowing systems and internal audit have significant positive effects on fraud prevention, with internal audit showing a stronger influence (β = 0.594; p < 0.001) compared to whistleblowing (β = 0.335; p < 0.001). The structural model explains 75.2% of the variance in fraud prevention outcomes. Dominant indicators were identified: accessibility of reporting channels (whistleblowing), compliance with audit international standards (internal audit), and consistent enforcement of ethical sanctions (fraud prevention). The study concludes that integrating effective whistleblowing mechanisms and high-quality internal audits is essential to strengthening fraud prevention strategies. These mechanisms must be supported by a governance environment that emphasizes ethical enforcement, transparency, and accountability. Practical implications are offered for public enterprises seeking to minimize fraud risk through internal governance reform